2021
DOI: 10.3390/ijerph18158023
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Mood State in Resident Physicians during COVID-19 Pandemic

Abstract: Since the novel coronavirus (SARS-CoV-2) has spread worldwide, healthcare workers—resident physicians in particular—have been hugely involved in facing the COVID-19 pandemic, experiencing unprecedented challenges in fighting the disease. We aimed to evaluate the prevalence of poor sleep quality, daytime sleepiness, and alterations in mood state profiles in this category. This cross-sectional study, conducted in 2020, enrolled 119 subjects from a university hospital in southern Italy. Epworth Sleepiness Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 29 publications
2
26
4
2
Order By: Relevance
“…Moreover, the study showed that the staff working with patients infected with the SARS-CoV-2 virus reported a higher level of occupational burnout and lower level of job satisfaction than the staff working with patients not infected with the SARS-CoV-2 virus [17]. Other studies also confirmed a high intensity of stress (24 according to PSS-10), as well as symptoms of depression, anxiety and insomnia among healthcare staff working with patients infected with SARS-CoV-2 [18][19][20], especially among women [21][22][23], which tended to increase along with respondents' age [24]. No relationship between age and the level of intensity of stress was found in the authors' own study.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the study showed that the staff working with patients infected with the SARS-CoV-2 virus reported a higher level of occupational burnout and lower level of job satisfaction than the staff working with patients not infected with the SARS-CoV-2 virus [17]. Other studies also confirmed a high intensity of stress (24 according to PSS-10), as well as symptoms of depression, anxiety and insomnia among healthcare staff working with patients infected with SARS-CoV-2 [18][19][20], especially among women [21][22][23], which tended to increase along with respondents' age [24]. No relationship between age and the level of intensity of stress was found in the authors' own study.…”
Section: Discussionmentioning
confidence: 93%
“…Coronavirus disease (COVID- 19), which started in Wuhan, China, in December 2019, became a pandemic in a few months, leading to extraordinary risks to human beings [1]. Despite the majority of infected subjects having a moderate illness and about 10-15% of patients developing grave complications [2], until 21 October 2021, about 4.9 million deaths were declared, with over 241 million cases confirmed globally [3].…”
Section: Introductionmentioning
confidence: 99%
“…The considerable psychological impact of the COVID-19 pandemic has undoubtedly influenced feelings and behaviors [ 18 , 19 ], requiring the adoption of coping strategies to play a buffering role on stress and have a preventive effect on mental health [ 20 ]. Different coping strategies are used depending on external factors (such as cultural and workplace context or geographical area) [ 21 ] and individual components (e.g., rage, terror, or sadness) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that a poor sleep quality can cause tiredness, thereby leading to reduced levels of alertness and amplified irritability [ 32 , 33 ]. Although our statistical models did not find gender as a predictor of poor sleep quality, more women than men (10 vs. 0) complained about nightmares, resulting in a statistically significant gender difference and confirming that women are more susceptible to sleep disturbances [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 72%